Multifocal Pigmented Villonodular Synovitis in the Noonan Syndrome - Othmane Miri; Nicolas Bonnet; Philippe Lysy; Naima Loucheur; René Gayito; Pierre Louis Docquier (Case Reports in Orthopedics)
Noonan-like/multiple giant cell lesion (NS/MGCL) is a rare condition overlapping with Noonan syndrome. Once thought to be a specific and separate entity, it is now suggested to be a variant of the Noonan syndrome spectrum. We report the case of an 8-year-old boy with a typical clinical picture of Noonan syndrome with a de novo germline mutation of PTPN11 (c.854 T>C). During his follow-up, the patient developed multifocal pigmented villonodular synovitis which first affected the left knee and shortly after both elbows.